Industrial By-products used in a Landfill Cover - Nordmark, Desiree; Andreas, Lale; Lagerkvist, Anders (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2014)
A small industrial waste landfill in Obbola, Northern Sweden is being completed and a final cover is installed. The landfill is owned and used by SCA Packaging, a paper mill factory nearby. An alternative final cover will be used, consisting mainly of industrial by-products from the paper mill. The aim of using industrial by-products is to save virgin materials, not to use synthetic materials and to make a cost-effective and environmentally safe closure of the landfill, while relevant laws and regulations are complied to. Godkänd; 2014; 20141119 (desnor)